2011
DOI: 10.1016/j.ultsonch.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sonolytic, sonocatalytic and sonophotocatalytic degradation of chitosan in the presence of TiO2 nanoparticles

Abstract: The degradation of chitosan by means of ultrasound irradiation and its combination with heterogeneous (TiO(2)) was investigated. Emphasis was given on the effect of additives on degradation rate constants. Ultrasound irradiation (24 kHz) was provided by a sonicator, while an ultraviolet source of 16 W was used for UV irradiation. The extent of sonolytic degradation increased with increasing ultrasound power (in the range 30-90 W), while the presence of TiO(2) in the dark generally had little effect on degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…A desired concentration of DDVP was prepared by dissolving the 12 L of dechlorinated tap water aerated for 40 min at room temperature (19)(20)(21)(22)(23)(24)(25) o C). Then, the catalyst was added to the above DDVP solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A desired concentration of DDVP was prepared by dissolving the 12 L of dechlorinated tap water aerated for 40 min at room temperature (19)(20)(21)(22)(23)(24)(25) o C). Then, the catalyst was added to the above DDVP solution.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have been reported on combining ultrasound with UV light irradiation in the presence of TiO 2 and sonophotocatalysis can enhance the efficiency of semiconductor mediated degradation of organic contaminants synergistically. [18][19][20] To the best of our knowledge, the combination of radial ultrasound and magnetic core-shell photocatalyst was seldom reported. Radial ultrasound can increase the distribution area of ultrasound wave, thus increasing the amounts of the reactive radical species.…”
Section: -17mentioning
confidence: 99%
“…Actually the ultrasound promoted reactions increased the catalytic activity of TiO 2 by de-aggregating the catalyst particles, thus increasing the surface area for the reaction. Secondly, the increased production of hydroxyl radicals as per the following reactions [22]:…”
Section: Synergistic Effect With Ultrasoundmentioning
confidence: 99%
“…The rate of chitosan degradation in mentioned conditions (sonophotocatalysis) increased with an increase in catalyst loading. The beneficial effect of coupling photocatalysis with sonolysis may be attributed to several reasons, namely: (i) increased production of hydroxyl radicals in the reaction mixture, (ii) enhanced mass transfer between the liquid phase and the catalyst surface, (iii) catalyst excitation by ultrasound-induced luminescence which has a wide wavelength range below 375 nm [63][64][65][66] and (iv) increased catalytic activity due to ultrasound de-aggregating catalyst particles, thus increasing surface area.…”
Section: Sonophotocatalytic (Us+uv+tio 2 ) Degradation Of Hydrogelmentioning
confidence: 99%